Following of Protocols for Chest Drain Insertion-an Audit Report - Ali, Sara; Abid, Wajeeha; Khan, Asad Iqbal; Raza, Ali; Abu Bakar; Hassan (Indus Journal of Bioscience Research, 2025)
Background: Chest drain insertion is a common, potentially life-saving procedure indicated for conditions such as pneumothorax, hemothorax, and pleural effusion. Despite the availability of evidence-based guidelines from the British Thoracic Society (BTS), variable adherence has been reported, with lapses in essential steps such as aseptic technique, clotting disorder assessment, and provision of analgesia. Inadequate compliance with protocols can increase the risk of complications, underscoring the need for regular audits. Objective: To evaluate adherence to BTS chest drain insertion protocols in a tertiary care hospital, identify deficiencies in practice, implement corrective interventions, and assess improvement through re-audit. Methodology: A prospective, closed-loop clinical audit was conducted in the Department of Pulmonology and Internal Medicine of a tertiary care teaching hospital in Pakistan. All adult patients (≥18 years) undergoing chest drain insertion over a four-week period were included, with emergency cases also considered to reflect real-world practice. Baseline data were collected prospectively using a structured proforma aligned with BTS standards. Following presentation of results and reinforcement of protocols through departmental teaching, a re-audit was conducted two weeks later using the same methodology. Compliance with each standard was analyzed descriptively and presented as percentages. Results: The baseline audit revealed an overall compliance rate of 81.3%. High adherence was observed in consent taking, imaging guidance, and insertion technique, while moderate compliance was noted in aseptic practice, securing of drains, and post-procedure chest X-rays. Assessment of clotting disorders in non-urgent cases demonstrated poor adherence (